PENGARUH MODEL PEMBELAJARAN TTW BERBANTUAN MEDIA GAMBAR TERHADAP KOMPETENSI PENGETAHUAN IPA SISWA KELAS V SD - ., Ni Made Ayu Agustina Mas Sriati; ., Drs. I Nengah Suadnyana,M.Pd; ., Dra. Ni Nyoman Ganing, M.Hum (Universitas Pendidikan Ganesha, 2017)
Tujuan penelitian ini adalah untuk mengetahui perbedaan yang signifikan kompetensi pengetahuan IPA antara kelompok siswa yang dibelajarkan menggunakan model pembelajaran TTW berbantuan media gambar dan yang dibelajarkan menggunakan pembelajaran konvensional siswa kelas V SD Gugus Moch Hatta Kecamatan Denpasar Selatan Tahun Pelajaran 2016/2017. Jenis penelitian ini merupakan eksperimen semu dengan menggunakan desain penelitian nonequivalent control group design. Populasi penelitian ini adalah seluruh siswa kelas V SD gugus Moch Hatta Denpasar Selatan Tahun Pelajaran 2016/2017 yang banyaknya 271 orang. Sampel ditentukan dengan random sampling dengan mengacak kelas. Sampel dalam penelitian ini adalah kelas V SD Negeri 3 Panjer sebagai kelompok eksperimen berjumlah 50 orang dan kelas V SD Negeri 2 Panjer sebagai kelompok kontrol dengan berjumlah 47 orang. Data kompetensi pengetahuan IPA dikumpulkan dengan instrumen berupa tes pilihan ganda biasa berjumlah 29 butir tes yang telah divalidasi. Data kompetensi pengetahuan IPA dianalisis dengan t-test. Hasil analisis menunjukkan bahwa terdapat perbedaan yang signifikan kompetensi pengetahuan IPA antara kelompok siswa yang dibelajarkan menggunakan model pembelajaran TTW berbantuan media gambar dan yang dibelajarkan menggunakan pembelajaran konvensional siswa kelas V SD Gugus Moch Hatta Denpasar Selatan Tahun Pelajaran 2016/2017. Hal tersebut dibuktikan dengan hasil thitung= 6,050 > ttabel = 1,980 pada taraf signifikansi 5% dengan dk=95. Demikian pula nilai Rerata kompetensi pengetahuan IPA siswa kelompok eskperimen = 82,42 > = 74,51 rerata kompetensi pengetahuan IPA siswa kelompok kontrol. Dengan demikian dapat disimpulkan bahwa model pembelajaran TTW berbantuan media gambar berpengaruh terhadap kompetensi pengetahuan IPA siswa kelas V SD Gugus Moch Hatta Denpasar Selatan Tahun Pelajaran 2016/2017.Kata Kunci : TTW, media gambar, IPA The purpose of this study was to find out the significant differences in the science knowledge competence between students who was studied by using TTW assisted images media with students who was studied by using the conventional learning in class V SD Gugus Moch Hatta south Denpasar district academic year 2016/2017. This type of research was a quasi-experimental research using non equivalent control group design. The purpose of this study was to find out the significant differences in the science knowledge competence between students who was studied by using TTW assisted images media with students who was studied by using the conventional learning in class V SD Gugus Movh Hatta south Denpasar district academic year 2016/2017. This type of research was a quasi-experimental research using non equivalent control group design. The population in this research were all students in the fifth grade of elementary school of SD Gugus Moch Hatta south Denpasar district academic year 2016/2017, which is the total of students are 271 person. The samples were taken with a random sampling technique to randomize the class. The sample in this study is the class V of SD Negeri 3 Panjer as the experimental group, which is the total of 50 person and class V of SD Negeri 2 Panjer as a control group, which is the total of 47 person. Therefore, The data of Science knowledge competence were collected by instruments in the form of an objective test , which objective test consist of 29 items in valid. The data of science knowledge competence were analyzed by t - test. The analysis stated that there were the significant differences in the science knowledge competence between students who was studied by using TTW assisted images media with students who was studied by using the conventional learning in class V SD Gugus Moch Hatta south Denpasar district academic year 2016/2017. This study was evidenced by the results ( thit = 6,050 > t table = 1,980 ) with db =( n1 + n2 - 2 = 97-2 = 95 ) and a significance level of 5 %. Similarly, the average value obtained in experimental group learning outcomes ( 82,42 ) is greater than the control class ( 74,51 ). However, Based on the result above it can be concluded that the application of TTW assisted images media had an effect in science knowledge competence in class V SD Gugus Moch Hatta south Denpasar district academic year 2016/2017.keyword : TTW, images media, science